2006
DOI: 10.1080/07399330600803766
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death Among Patients With Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome (CFS) is a debilitating illness affecting thousands of individuals. At the present time, there are few studies that have investigated causes of death for those with this syndrome. The authors analyzed a memorial list tabulated by the National CFIDS Foundation of 166 deceased individuals who had had CFS. There were approximately three times more women than men on the list. The three most prevalent causes of death were heart failure, suicide, and cancer, which accounted for 59.6% of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 26 publications
2
58
1
Order By: Relevance
“…We believe this is the first time that vascular endothelial dysfunction has been measured directly in ME/CFS patients, and these findings build on previous work reporting indirect markers of endothelial dysfunction, such as increased oxidative stress [4,10], inflammation [5,11] and arterial stiffness [5]. This evidence collectively points to increased cardiovascular risk in ME/CFS patients, which is borne out epidemiologically by their high mortality due to heart disease [12].…”
mentioning
confidence: 50%
“…We believe this is the first time that vascular endothelial dysfunction has been measured directly in ME/CFS patients, and these findings build on previous work reporting indirect markers of endothelial dysfunction, such as increased oxidative stress [4,10], inflammation [5,11] and arterial stiffness [5]. This evidence collectively points to increased cardiovascular risk in ME/CFS patients, which is borne out epidemiologically by their high mortality due to heart disease [12].…”
mentioning
confidence: 50%
“…In an attempt to assess CFS-related mortality, Jason et al (2006) analyzed a national CFS foundation Memorial List containing the names of individuals with CFS who had died. They found the mean age of death for heart failure (59 years), cancer (48 years), and suicide (39 years) among those with CFS was considerably younger than the mean age of deaths in the general population from heart failure (83 years), cancer (72 years), and suicide (48 years), suggesting that CFS might have increased the risk of death for at least this sample.…”
Section: A Contested Illnessmentioning
confidence: 99%
“…In addition to the increased mortality due to these causes, the 2006 Jason and 2016 McManimem studies also reported that these deaths occurred at a significantly earlier age than normal [31,33].…”
Section: Usmentioning
confidence: 99%
“…However, studies by , March (2014), and McManimen (2016) have documented abnormally high levels of death due to cancer, cardiovascular disease, and suicide [31][32][33]. Jason analyzed a memorial list of 166 deceased individuals and reported that approximately 20% died of each of these three causes.…”
Section: Estimating Yllmentioning
confidence: 99%